Salmonella Diversity Along the Farm-to-Fork Continuum of Pastured Poultry Flocks in the Southeastern United States - Rothrock, Michael J.; Guard, Jean Y.; Oladeinde, Adelumola (Frontiers in Animal Science, 2021)
Greater consumer demand for all natural, antibiotic-free poultry products has led to an increase in pastured poultry operations. Given the increased level of environmental interaction, and the potential increase in exposure to foodborne pathogens, a greater understanding of the prevalence and diversity of Salmonella populations inherent within pastured poultry flocks. To achieve this, 42 pastured poultry flocks from 11 farms were sampled using a farm-to-fork strategy and Salmonella was isolated and characterized through pre-harvest (feces, soil) to post-harvest (ceca, whole carcass rinse) to the final product (whole carcass rinse) the consumer would purchase. Salmonella was isolated from 353 of a total of 2305 samples, representing an overall prevalence of 18.1%. By far the most prevalent serotype was Kentucky (72.7% of all isolates), with less than 16% of all Salmonella representing a top serotype of concern for human health according to the CDC. Even though these flocks were raised antibiotic-free, Salmonella isolates exhibited resistances to a variety of antibiotics, with the two most common resistances being towards tetracycline and streptomycin (68.8% and 64.4% of all isolates, respectively); however, almost 98% of the multidrug resistant isolates were serotype Kentucky. Salmonella prevalence and diversity (both in terms of serotypes and antibiotic resistance profiles) were related more to the farm location than to the type of sample from which the Salmonella was isolated from along the farm-to-fork continuum. Based on these data, while Salmonella prevalence was similar to that from conventional poultry operations, serotypes of lesser concern to human health (Kentucky, Indiana) tended to fill the ecological niche for Salmonella species throughout the farm-to-fork continuum in these pastured poultry flocks. The diversity of these Salmonella populations tended to be farm specific, indicating the need for more tailored intervention strategies to continue to enhance the safety of these products.